SOCS-1 is involved in TNF-α-induced mitochondrial dysfunction and apoptosis in renal tubular epithelial cells. Issue 5 (October 2017) - Du, Chunyang; Yao, Fang; Ren, Yunzhuo; Du, Yunxia; Wei, Jinying; Wu, Haijiang; Duan, Huijun; Shi, Yonghong
Highlights: TNF-α induced expression of SOCS-1. Overexpression of SOCS-1 inhibited mitochondrial dysfunction, oxidative stress and apoptosis induced by TNF-α. Overexpression of SOCS-1 inhibited activation of JAK/STAT signaling pathway induced by TNF-α. Abstract: Tumor necrosis factor-α (TNF-α) is suggested to induce mitochondrial dysfunction and apoptosis of renal tubular epithelial cells that possibly exacerbates renal function in chronic kidney disease (CKD). Here we investigated whether suppressor of cytokine signaling-1 (SOCS-1), an inhibitor of cytokine signaling, was involved in TNF-α-induced human renal tubular epithelial cells (HKCs) oxidative stress and apoptosis. TNF-α promoted the protein and mRNA expression of SOCS-1 in a time and dose dependent manner, along with increased cell apoptosis and activation of apoptosis signal regulating kinase-1(ASK1) in HKCs. Furthermore, overexpression of SOCS-1 in HKCs reduced TNF-α-mediated oxidative stress and apoptosis. Meanwhile, We also found that overexpression of SOCS-1 could regulate the activity of JAK/STAT signaling pathway. In addition, a specific JAK2 inhibitor, AG490, that both attenuated TNF-α-induced oxidative stress, also reduced apoptosis. Taken together, overexpression of SOCS-1 prevented TNF-α-mediated cell oxidative stress and apoptosis may be via suppression of JAK/STAT signaling pathway activation in HKCs.